2021
DOI: 10.13057/asianjagric/g050203
|View full text |Cite
|
Sign up to set email alerts
|

Variation in winged bean (Psophocarpus tetragonolobus) growth parameters, seed yield, nodulation, and nitrogen fixation

Abstract: Abstract. Adegboyega TT, Abberton MT, Abdelgadir AH, Mahamadi D, Olaniyi OA, Ofodile S, Babalola OO. 2021. Variation in winged bean (Psophocarpus tetragonolobus) growth parameters, seed yield, nodulation, and nitrogen fixation. Asian J Agric 5: 61-71. Underutilized legumes are widely distributed in tropical agriculture and associated with low yield.  Thus they have not really been fully explored due to lack of research investment, breeding programs targeting crop improvement, marketing, and low awareness of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Thus, the significant variation in the grain yield observed in this study across the three locations clearly indicated that there was sufficient genetic diversity, which will aid selecting the right genotypes for improvement. This finding is consistent with the findings of Adegboyega et al (2021) and Mohanty et al (2013), who found significant Table 4 shows the mean seed yield across the twenty genotypes of winged bean observed in six environments.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the significant variation in the grain yield observed in this study across the three locations clearly indicated that there was sufficient genetic diversity, which will aid selecting the right genotypes for improvement. This finding is consistent with the findings of Adegboyega et al (2021) and Mohanty et al (2013), who found significant Table 4 shows the mean seed yield across the twenty genotypes of winged bean observed in six environments.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, inoculation with FA3 strains enhanced TVSu-1739 more than other inoculated BGN genotypes in nodules number and weight and nitrogen fixed both in Ibadan and Ikenne in both years, but there were no significant differences recorded among TVSu-1,698, TVSu-475, and TVSu-365 ( Table 5 ). In the glasshouse, bacteria strain inoculation also enhanced the nodulation and nitrogen derived from the atmosphere of BGN genotypes compared to the uninoculated control in both sterile and non-sterile soil, which is related to a study conducted by Adegboyega et al (2021) , which revealed that the results recorded in nitrogen fixation and nitrogen derived from the atmosphere in the shoot and root of wing bean genotypes. Inoculation with B. japonicum strains significantly enhanced nodule number and nitrogen derived from the atmosphere in TVSu-787 and TVSu-475, respectively, compared to other inoculated BGN genotypes ( Table 8 ).…”
Section: Discussionsupporting
confidence: 66%
“…Based on a study conducted by Yakubu et al (2010) , BGN has a high nitrogen fixing potential, provided that an effective and appropriate rhizobium strain is used as an inoculant and that the plant nutrient requirements other than nitrogen are readily available in the soil. Adegboyega et al (2021) reported that the amount of N fixed (kg ha −1 ) in the shoot of wing bean varies among accessions. Zoundji et al (2022) concluded that the inoculation of Bambara groundnut with rhizobia improved nodulation and dry biomass yield and enhanced nitrogen uptake.…”
Section: Introductionmentioning
confidence: 99%
“…For example, accession MYO-01 has quite small pods (a mature pod length of around 11 cm, half that of accessions CHIMBU and MYAN-05), but studies elsewhere have shown that high vegetable pod yields are correlated with pod length and weight more so than with pod number (Kesavan and Erskine 1980, in Papua New Guinea;Yulianah et al 2020, in Indonesia). Similar germplasm evaluations in various locations have shown considerable diversity in pod characteristics, including pod length, width and weight, and pod color, shape, and texture (Khan 1982;Kuswanto et al 2016;Kant and Nandan 2018;Sarode Hemal and Dodake 2019;Adegboyega et al 2019Adegboyega et al , 2021Laosatit et al 2021;Chankaew et al 2022) that could provide nutritional diversity and novelty in competitive commercial vegetable markets.…”
Section: Discussionmentioning
confidence: 99%